A Chimeric SERM–Histone Deacetylase Inhibitor Approach to Breast Cancer Therapy. Issue 3 (16th August 2013) - Patel, Hitisha K.; Siklos, Marton I.; Abdelkarim, Hazem; Mendonca, Emma L.; Vaidya, Aditya; Petukhov, Pavel A.; Thatcher, Gregory R. J.
Abstract Breast cancer remains a significant cause of death in women, and few therapeutic options exist for estrogen receptor negative (ER (−)) cancers. Epigenetic reactivation of target genes using histone deacetylase (HDAC) inhibitors has been proposed in ER (−) cancers to resensitize to therapy using selective estrogen receptor modulators (SERMs) that are effective in ER (+) cancer treatment. Based upon preliminary studies in ER (+) and ER (−) breast cancer cells treated with combinations of HDAC inhibitors and SERMs, hybrid drugs, termed SERMostats, were designed with computational guidance. Assay for inhibition of four type I HDAC isoforms and antagonism of estrogenic activity in two cell lines yielded a SERMostat with 1–3 μM potency across all targets. The superior hybrid caused significant cell death in ER (−) human breast cancer cells and elicited cell death at the same concentration as the parent SERM in combination treatment and at an earlier time point.